2018
DOI: 10.1111/jace.15729
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the intragranular microstructure in ceramic nanocomposites and their effect on the mechanical properties

Abstract: The formation of intragranular microstructure in Al2O3/ZrO2 and Si2N2O/Si3N4 nanocomposites was analyzed, and the effect of intragranular microstructure on the mechanical properties of nanocomposites was investigated. Results suggest 3 requisite conditions for the formation of intragranular microstructure and the role of intracrystalline glass phase and scar microstructure. In case of Al2O3/ZrO2, the intragranular microstructure leads to the formation of transgranular fracture, which in turn improves the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Luo et al . [16] and Chen et al . [18] obtained a similar conclusion that abnormal growth of Al 2 O 3 and normal growth of ZrO 2 leads to the formed of intragranular ZrO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Luo et al . [16] and Chen et al . [18] obtained a similar conclusion that abnormal growth of Al 2 O 3 and normal growth of ZrO 2 leads to the formed of intragranular ZrO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Intragranular ZrO 2 increases the strength of the main grain boundaries around but decreases the strength of matrix grain by producing a large number of sub‐grain boundaries and micro‐cracks. As a result, the fracture mode has been transformed from intergranular fracture to transgranular fracture, to improve the comprehensive mechanical properties of ZTA ceramics [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excellent properties of ceramics such as high hardness, resistance to abrasion, erosion, and corrosion, absence of chemical interaction in the working medium and with the environment, and low thermal expansion make them unreplaceable for the aviation and aerospace industry and in other important applications [33, 34, 35, 36, 37, 38, 39, 40]. In medicine, ceramic implants show their reliability, high wear resistance, absence of metal ion accumulation, reduced risk of revision surgery, and negative consequences [41, 42, 43].…”
Section: Introductionmentioning
confidence: 99%
“…5 Herein, it is, in principle, feasible to develop novel lightweight refractories by synthesizing Al 2 O 3 -ZrO 2 composites. [13][14][15][16][17] Using solution blow spinning and atomic layer deposition (ALD), Xu et al produced novel Al 2 O 3 nanotube aerogels having a pore size of 1-2 mm, whose thermal conductivity is only 0.022 W m À1 K À1 at room temperature. 7 Nevertheless, few studies have reported the thermal performance of Al 2 O 3 -ZrO 2 composites at a high temperature (900-1600 C) till now.…”
Section: Introductionmentioning
confidence: 99%